(untitled) (Medico Legal Update, 2019)
Aim: The objective of this study was to assess the Quality of Life on the patients with maxillofacial injuries. Materials and Method: A cross-sectional prospective study was designed to identify patients admitted with maxillofacial injuries from June 2017 to February 2018. Details regarding the social demographics,nature and severity of injury,and treatment methods were recorded. To assess the Quality of Life,Short Form-36 Version 2.0(SF-36v2)questionnaire was administered with recall period of 4 weeks. Analysis involved descriptive statistics and box plots to correlate the quality of life among various age groups and gender. Results: A total of 129 patients with maxillofacial injuries were identified(115 males, 14 females;mean age = 35.14 years).Road traffic accidents were the cause of injury in 104 patients (80.62%)and slip and fall accounting for 66.7% among the elderly population of above 60 years. Only 36.4% underwent open reduction mode of treatment while the rest were managed conservatively. The overall Quality of life among male and female was not statistically significant,however when correlated with different age groups significant results were seen among the elderly and the middle age group.